Case Study: A Japanese patient with metastatic renal cell carcinoma who achieved long‐term treatment‐free survival with pembrolizumab and axitinib in the KEYNOTE‐426 phase III trial of pembrolizumab and axitinib versus sunitinib - Koshiro Nishimoto (IJU Case Reports, 2022)
Introduction Our patient treated with pembrolizumab and axitinib is one of the longest survivors in Japan on KEYNOTE 426, despite adverse events, including delayed‐onset hepatitis. We herein present a detailed clinical course and short discussion on the case. Case presentation This was a 49‐year‐old male with clear cell renal cell carcinoma and lung metastases. After cytoreductive nephrectomy, treatment with pembrolizumab plus axitinib was initiated and the patient demonstrated a radiographic partial response as best response. The main adverse event was pembrolizumab‐induced delayed‐onset hepatitis, which was successfully treated with prednisolone. Pembrolizumab was re‐initiated and completed. Conclusion The survival benefit in the present case may be due to the initial potent anti‐cancer effects of axitinib and durable immune effects of pembrolizumab, leading to long‐term treatment‐free survival.